2015
DOI: 10.1039/c5nr01568e
|View full text |Cite
|
Sign up to set email alerts
|

A dual wavelength-activatable gold nanorod complex for synergistic cancer treatment

Abstract: A multifunctional gold nanorod (AuNR) complex is described with potential utility for theranostic anticancer treatment. The AuNR was functionalized with cyclodextrin for encapsulation of doxorubicin, with folic acid for targeting, and with a photo-responsive dextran-azo compound for intracellular controlled drug release. Interaction of AuNR complex toward HeLa cells was facilitated via the folic acid targeting ligand as displayed in the dark-field images of cells. Enhanced anticancer efficacy was demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 66 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…The PTT effect of AuNR can be used not only for photosensitizer releasing but also for the cancer therapy. 43,58,59 Therefore, the cell viability after being treated with post-modified AuNR and irradiated by 808 nm laser light or by 808 and 635 nm laser lights was evaluated. The results showed that AuNR corresponding to 4 µg/mL and 8 µg/mL AuNR-AlPcS 4 inhibited the growth of cells by about 30% and 50%, respectively.…”
Section: Cytotoxicity and Anti-growth Effect Assay Of Different Drug mentioning
confidence: 99%
“…The PTT effect of AuNR can be used not only for photosensitizer releasing but also for the cancer therapy. 43,58,59 Therefore, the cell viability after being treated with post-modified AuNR and irradiated by 808 nm laser light or by 808 and 635 nm laser lights was evaluated. The results showed that AuNR corresponding to 4 µg/mL and 8 µg/mL AuNR-AlPcS 4 inhibited the growth of cells by about 30% and 50%, respectively.…”
Section: Cytotoxicity and Anti-growth Effect Assay Of Different Drug mentioning
confidence: 99%
“…A quite recent study quantified the cellular uptake by GNRs in MCF-7 cells by using inductively coupled plasma mass spectrometry, and the MCF-7 cells used the micropinocytosis mechanism to internalize bare GNRs that aggregate and associate with the cell membrane [ 61 ]. Pacardo et al discovered that when functionalized with cyclodextrin, gold nanorods can encapsulate doxorubicin (DOX), and the as-formed nanocomplex showed enhanced anti-cancer efficacy [ 62 ]. Zhang et al reported DNA-conjugated gold nanorods as a multifunctional carrier, which can load and release DOX at targeted locations [ 63 ].…”
Section: Gold Nanostructures For Cancer Treatmentmentioning
confidence: 99%
“…Gold-based (Au) nanostructures comprise another dominant class of PAI contrast agents. Gold nanostructures, such as nanorods (NRs) [ 44 , 53 , 54 , 55 ], nanocages (NCs) [ 37 , 56 , 57 , 58 ], and nanospheres (NSs) [ 59 ], have strong and tunable optical absorption due to localized surface plasmon resonance (LSPR) effect, where the free charges on the surface of the Au nanostructures oscillate with the electromagnetic field. Additionally, the absorption region can be adjusted as a result of change in resonance frequency by modulating the size and shape of the Au nanostructures [ 60 ].…”
Section: Inorganic Nanomaterials-based Photoacoustic Therapymentioning
confidence: 99%